2021
DOI: 10.3389/fcell.2021.733183
|View full text |Cite
|
Sign up to set email alerts
|

Normothermic ex vivo Heart Perfusion Combined With Melatonin Enhances Myocardial Protection in Rat Donation After Circulatory Death Hearts via Inhibiting NLRP3 Inflammasome-Mediated Pyroptosis

Abstract: ObjectiveThe adoption of hearts from donation after circulatory death (DCD) is a promising approach for the shortage of suitable organs in heart transplantation. However, DCD hearts suffer from serious ischemia/reperfusion injury (IRI). Recent studies demonstrate that nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome-mediated pyroptosis is a novel target to ameliorate myocardial IRI. Melatonin is shown to inhibit NLRP3 inflammasome-mediated pyroptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Cardiomyocytes secreted exosomes containing circHIPK3 under hypoxic conditions to protect injured cardiomyocytes. In addition, the inflammatory response is involved in all aspects of I/R injury ( 25 , 30 ). Chen et al ( 31 ) found that eNOS activation in cardiac microvascular endothelial cells (CMECs) required a crosstalk between cardiomyocytes (CMs) and CMECs through the uptake of CM-derived sEVs.…”
Section: Mechanism Of Evs Repairing Damaged Myocardiummentioning
confidence: 99%
“…Cardiomyocytes secreted exosomes containing circHIPK3 under hypoxic conditions to protect injured cardiomyocytes. In addition, the inflammatory response is involved in all aspects of I/R injury ( 25 , 30 ). Chen et al ( 31 ) found that eNOS activation in cardiac microvascular endothelial cells (CMECs) required a crosstalk between cardiomyocytes (CMs) and CMECs through the uptake of CM-derived sEVs.…”
Section: Mechanism Of Evs Repairing Damaged Myocardiummentioning
confidence: 99%
“…Oxidative stress has been shown to contribute to the activation of NLRP3 inflammation and pyroptosis ( 29 ). It was previously demonstrated that ROS enhance the assembly of NLRP3, ASC and caspase-1, which lead to the mutation of cleaved caspase-1( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of ESHP, preclinical studies report induction of the markers of oxidative stress and inflammation during ESHP in both perfusate and myocardial tissue even in the negligible damaged animal hearts (as opposed to DCD models) (19,63,139), even with a leukocyte-depleted perfusate (140). In a study of ESHP of DCD rat hearts by Lu et al, melatonin attenuated the induction of IL-11b, IL-18, IL-6 and TNF-a as well as the markers of oxidative injury such as malondialdehyde and 4-hydroxynonenal in the myocardial tissue, resulting in superior functional status (141). However, in a DCD porcine model of ESHP, Sandha et al showed that attenuating of the induction of the inflammatory responses during ESHP, although lead to lower edema formation in the heart, was not associated with improvement of myocardial function during ESHP.…”
Section: Clinical Significance Of Inflammation and Oxidative Stressmentioning
confidence: 98%